2007
DOI: 10.1152/ajplung.00294.2006
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 stimulates the expression of CXCL-8, E-selectin, VEGF, and inducible nitric oxide synthase mRNA by equine pulmonary artery endothelial cells

Abstract: stimulates the expression of CXCL-8, E-selectin, VEGF, and inducible nitric oxide synthase mRNA by equine pulmonary artery endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 59 publications
3
27
1
Order By: Relevance
“…induces VCAM-1 expression in cultured endothelial cells (15). Consistent with these data, incubation of human umbilical vein endothelial cells (HUVECs) with 20 ng/ml IL-4 resulted in a time-dependent increase in IL-4 mRNA, as measured by realtime PCR, with peak levels (39.6-fold) occurring at 24 h (Fig.…”
Section: Il-4 Induces Vcam-1 But Not Icam-1 Expression In Cultured Ensupporting
confidence: 81%
See 1 more Smart Citation
“…induces VCAM-1 expression in cultured endothelial cells (15). Consistent with these data, incubation of human umbilical vein endothelial cells (HUVECs) with 20 ng/ml IL-4 resulted in a time-dependent increase in IL-4 mRNA, as measured by realtime PCR, with peak levels (39.6-fold) occurring at 24 h (Fig.…”
Section: Il-4 Induces Vcam-1 But Not Icam-1 Expression In Cultured Ensupporting
confidence: 81%
“…Activation of the receptor results in Janus kinase 1/2 (JAK-1/2)-dependent tyrosine phosphorylation and subsequent dimerization of signal transducer and activation of transcription 6 (STAT6), which then translocates to the nucleus and binds to consensus sequences (TTCN 3-4 GAA) found within promoters of IL-4-regulated target genes (14,27). Previous studies with endothelial cells have demonstrated that IL-4 induces the expression of CXCL-8, inducible nitric oxide synthase (iNOS) (15), urokinase-type plasminogen activator (u-PA) (46), vascular endothelial growth factor (VEGF) (15), P-selectin (20,32,47), monocyte chemoattractant protein 1 (MCP-1) (39), CCL26 (18), , 15-lipoxygenase (24), and osteoprotegerin (41). In addition, previous studies have shown that IL-4 upregulates the expression of VCAM-1 in endothelial cells (4,10,14,23,26,37,40).…”
mentioning
confidence: 99%
“…iNOS mRNA levels were significantly increased 8.9-fold and 4.7-fold in response to BCG in 253J and T24 cells, respectively, relative to controls ( Figure 2, p < 0.001). As reported earlier, pretreatment of cells with 1400W inhibited BCG induced iNOS expression [16,17]. Compared to BCG, cells treated with 1400W prior to BCG exposure exhibited significantly decreased iNOS expression (7.5-and 4-fold in 253J and T24 cells, respectively, p<0.0001).…”
Section: Inos Expressionsupporting
confidence: 69%
“…Our results revealed that infected IL-4 -/-mice showed diminished leukocyte adhesion at 3 dpi when compared to infected WT mice. Previous studies have demonstrated that IL-4 regulates expression of adhesion molecules, with an upregulatory effect on vascular cell adhesion molecule-1 (VCAM-1) 22,23 and possibly on Pselectin 24,25 and a downregulatory effect on E-selectin 26,27 . It has also been reported that IL-4 can act synergistically with other cytokines, such as IL-1β and TNF-α, in order to promote lymphocyte binding to cultured microvascular endothelial cells 28,29 .…”
Section: Discussionmentioning
confidence: 99%